Hot melt extrusion aided amorphous solid dispersions of quercetin and resveratrol for solubility enhancement - Lakshmi Swapna Sai; Dasankoppa, Fatima S; Mutalik, Srinivas; Pisay, Muralidhar (Journal of Applied Pharmaceutical Research, 2025)
Background: Conversion of poorly soluble drugs into amorphous solid dispersions using different carriers is a formulation approach to improve solubility. Objective: The study investigates hot melt extrusion as an approach for producing amorphous solid dispersions that contribute to solubility enhancement. Methodology: Solid dispersions were hot melt extruded using two model compounds – quercetin and resveratrol with different carriers. The resulting solid dispersions were analyzed for solubility enhancement and characterized by various techniques. Results and Discussion: The solubility of solid dispersions was evaluated, revealing a 36-fold increase in the solubility of quercetin from 0.023 mg/ml to 0.823 mg/ml and a 97-fold increase in the solubility of resveratrol from 0.053 mg/ml to 5.125 mg/ml with soluplus as a carrier. Various characterization studies indicated the conversion of crystalline forms of quercetin and resveratrol into their amorphous forms, which was confirmed by powder x-ray crystallographic and scanning electron microscopic studies. In addition, the particle size reduction of quercetin reduced from 1.53 μm to 0.48 μm and resveratrol of 10.26 μm particle size was reduced to 0.22 μm in solid dispersions with soluplus as the carrier with decreased polydispersity index. Conclusion: This research demonstrates hot melt extrusion as a practical approach for fabricating amorphous solid dispersions.